Komparasi Media Pembelajaran Berbasis Audio Visual dengan Media Konvensional dalam Penguasaan Kosakata Bahasa Arab - Rosyada, Amrina; Sastrawan, Doni; Sari, Tri Maya (Al Mitsali : Jurnal Penelitian dan Pendidikan Bahasa Arab, 2024)
As technology develops in the era of modernization, the use of increasingly varied and sophisticated learning media has become an important effort to support the effectiveness of learning. One of the modern media that is commonly used is audio-visual based media. This type of media is assumed to make it easier for students to understand the material and is quite influential on student learning outcomes. However, based on observations, this type of media is still rarely applied in Islamic boarding school-based educational institutions, especially in Arabic language learning. This research aims to compare the application of conventional media and audio-visual media at the Darul Huffaz Pesawaran Islamic Boarding School. The research was conducted in class VII on Arabic language subjects, especially on vocabulary mastery material. This research seeks to analyze whether there are differences in the application of the two media. Based on quantitative analysis, the research results show that both media are equally effective and there is little difference in student learning outcomes through the application of conventional media and audio-visual media.